Smoking cessation for cancer patients through the lens of cancer specialists: challenges & solutions: Patricia Fitzpatrick. (25th October 2022) - Fitzpatrick, P; Bhardwaj, N; Syed, S; Fox, P; Frazer, K; Niranjan, V; Lyons, A; McCann, A; Brennan, S; Guerin, S
Abstract: Background: The benefits of smoking cessation (SC) for cancer patients are widely recognised. However, there has been a limited emphasis on SC in this context and it continues to be a challenge for cancer patients. As part of a larger feasibility study aiming to develop a structured SC pathway for cancer patients in Ireland, this qualitative study explored the SC practices, experiences and opinions of oncology healthcare professionals (HCPs). Methods: Semi-structured interviews were conducted with 18 HCPs from lung, breast, cervical, head and neck and general oncology, across 4 specialist adult cancer hospitals in Ireland. Interview transcripts were analysed using thematic analysis. Results: Four key themes emerged: (1) Frequently ask and advise but infrequently assist: most HCPs ask about smoking and many advise about available supports, but few refer patients to SC services. Where offered, referrals were to hospital SC services and/or nicotine replacement therapy was prescribed; no HCP prescribed varenicline or bupropion. Barriers included lack of time, ill-defined referral pathways and lack of knowledge. (2) Increased willingness but differing ability to quit: most patients were interested in quitting post diagnosis and had varying support needs, linked to cancer stage, social circumstances and stress levels. (3) Need for an integrated or parallel service: all HCPs suggested that a structured and defined referral pathway will facilitate SC. (4) Motivational counselling and pharmacotherapy combination: many HCPs suggested face to face as the best mode of intervention initially, with regular follow ups and ongoing support virtually, started pre-treatment, with an empathetic and empowering approach with provision of both motivational counselling and SC pharmacotherapy. Conclusions: Smoking post cancer diagnosis has serious implications for cancer treatment and prognosis but is frequently overlooked. These findings will inform the design of a SC pathway for cancer patients. Key messages: Despite increased willingness to quit, there is inadequate and inconsistent SC support provision for cancer patients. Tailored SC support should be an integral part of comprehensive cancer care.